Ir ao cinema: a formação inicial de professores e o instituinte ético-estético em educação nos processos formativos docentes - Miorando, Tania Micheline (2018)
Education opens to the cinema experience, bringing the ethical-aesthetic care in education to the initial formation, instituting itself from formative teaching processes. This is the doctoral thesis that I present to the Line of Research Training, Knowledge and Professional Development, of the Post-Graduation Program in Education, of the Federal University of Santa Maria (UFSM). The thesis proposed an investigation that aimed to analyze the teaching formative processes in the initial formation of teachers from the ethical-aesthetic institute in education, mobilized by the cinema. The research was devoted to linking ethical-aesthetic training with the education of deaf people, in the learning of Libras by teachers, who are listeners, in their initial formation, in order to consider the importance that the image has in everyday life and how much, contemporarily, this formation is an issue. The theoretical discussions were based on the Social Imaginary, by Cornelius Castoriadis, to discuss the Initial Formation of Teachers and the Cinema, always considering the territories of Teacher Training, Aesthetics, Ethics and the Cinema. The methodological devices were based on the research-training (JOSSO, 2004), from the narratives of teachers in initial formation who studied the Brazilian Sign Language. The narratives provoked by the cinema opened to a perspective of hermeneutic understanding (GADAMER, 2015) for calling to dialogue, in an exercise of approximation and understanding of the information, in view of the students' positions. The results show the power of the cinema and of the aesthetic experience as a provocative way to the formation of teachers and the imaginary that establishes education. The cinema was for this study a training device (SOUTO, 1999), provoking the cinema experience that called to dialogue, directing the look to the other by the aesthetics. Aesthetics went through time and became an ethical experience in teacher training. Ethics surveyed definitions that brought to its consideration concepts full of wealth that we lack to enhance in our relationships: alterity, sensitivity, the other, the difference. Teaching in initial formation gives space to break with the rationalism of curricular programs when one allows for readings nuanced with art, opening up to an aesthetic that allows education to escape from reductionist formalisms of closed curricula itself. This research reaffirmed the dialogue, provoked by the cinema in the formation of teachers and in the personal formation, instituting ethics and aesthetics in teaching.